Pengaruh Independen Pertumbuhan Penjualan, Dan Likuiditas Terhadap Kesulitan Keuangan (Studi Empiris atas Perusahaan Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia pada 2020-2023) - Aulia Nissa, Gina; Asmara, Rina Yuliastuty (UMSurabaya Publishing, 2025)
This study aims to determine the effect of Independent Commissioners, Sales Growth, and Liquidity on Financial distress. The type of research used is quantitative research. The population in this study were Property and Real Estate companies listed on the Indonesia Stock Exchange in 2020-2023. This sampling method was carried out by purposive sampling method and obtained 48 companies, with an observation year of 4 years, so that the total research data was 192. The research method used is causal model research. The type of data used in this study is secondary data. The data analysis method used is multiple linear regression analysis method with the help of IBM SPSS version 25. The results of this study prove that independent commissioners have no significant effect on financial distress, sales growth has no significant effect on financial distrees, but liquidity has a significant effect on financial distress.